AIDET communication combined with alternating prone ventilation for HIF-1α, sTREM-1 and hs-CRP in awake elderly patients with severe pneumonia - Wang, YanHong; Zhang, Rong; Li, XiaoYan; Deng, Xuejiao (Frontiers in Medicine, 2026)
BackgroundSevere pneumonia in elderly patients carries high mortality, with inflammatory markers such as HIF-1α, sTREM-1, and hs-CRP associated with disease severity. Combining alternating prone ventilation with AIDET communication may improve outcomes.ObjectiveTo evaluate the effects of AIDET communication combined with alternating prone ventilation on comfort, oxygenation, inflammatory markers, and prognosis in awake elderly patients with severe pneumonia.MethodsA total of 86 elderly patients were enrolled and assigned to either an AIDET group or a Conventional group (n = 43 each). Comfort scores, PaO2/FiO2 ratios, and serum levels of HIF-1α, sTREM-1, and hs-CRP were assessed at baseline and 72 h. Weaning success and time to withdrawal were also recorded.ResultsAt 72 h, the AIDET group demonstrated significantly higher comfort scores (T12: 8.3 ± 0.9 vs. 6.5 ± 1.1; p < 0.001) and improved oxygenation (PaO2/FiO2: 289.4 ± 23.5 vs. 231.2 ± 20.6; p < 0.001). Reductions in inflammatory markers were greater in the AIDET group: HIF-1α (↓24.3%; p < 0.001), sTREM-1 (↓22.7%; p = 0.003), and hs-CRP (↓28.1%; p < 0.001). Weaning success was higher in the AIDET group (95.3% vs. 76.7%; p = 0.013) with a shorter median time to weaning (47 h vs. 62 h; p < 0.001).ConclusionIn elderly patients with severe pneumonia, AIDET communication combined with prone ventilation significantly improves comfort, oxygenation, and biomarker profiles, and enhances weaning success. These findings support the integration of structured communication into respiratory care protocols.